Review of Malaysian Tenth Health Plan 2011-2015 - Ujan, Imran Anwar; Abdullah, Zainatul Shima; Haidar, Zulfiqar; Suhaimi, Mohd Adam (Islamic Countries Society of Statistical Sciences, 2017)
Malaysia is an energetic nation has appreciated monetary development on political soundness since his freedom. Malaysians are extra sound, have a more drawn out future and beneficial. The level of general health accomplished means that the achievement of the nation. Great health permits the nation to appreciate profitable and significant lifespan. Great health adds to the thriving and general social solidness. Tenth Malaysia Plan 2011-2015 has point by point on the health arrangement for country. There are 4 Technical Working Group was built up to deliver issues identified with health administrations conveyance, administration, and finance, health mindfulness and solid way of life and strengthening of individual and group to oversee own health.